Creation (and other) stories - Forgue, Amy Louise, author; Doenges, Judy, advisor; MacDonald, Bradley, committee member; Schwartz, Steven, committee member (Colorado State University. Libraries, 2010)
The following twelve stories explore the female experience through three generations of women, particularly the maternal relationships between these women as well as the ways that those relationships influence the characters’ interactions with men—their husbands and lovers. Much like my characters, each story functions individually and yet when considered in connection with the others gains deeper relevance and meaning for the reader. The collection is unified by character in that each of the stories centers around a small ensemble of recurring individuals, and through stories like “Creation,” “Honeymoon,” and “Quarry,” the three female characters unite to form a collective protagonist. However, each story is narrated in the voice of the third generation character, who ultimately, through the act of telling her mother’s and grandmother’s stories as well as her own, emerges as a narrator-protagonist to further unify the collection as a whole. These women are united not only by their shared experiences but also by their common history, namely their Native American ancestry, and as such thematic patterns emerge from story to story and from one generation to the next. This ancestral mythos haunts their stories and their lives in a way that further informs and connects the collection on both a symbolic and an aesthetic level.
Covers not scanned.
Keywords: Stories, plots, etc; Women; Generations in literature